A survey of the flora and vegetion of the Mayville Ledge Beech-Maple Woods State Natural Area - (:unkn) unknown (My University, 1989)
At least 132 vascular plant species were present in two relatively undisturbed woods in the Mayville Ledge Natural Area. The Plateau Woods was dominated by ironwood (Ostrya virginiana), American beech (Fagus grandifolia), and sugar maple (Acer saccharum), with a Continuum Index of 2535. Red oak (Quercus rubra), basswood (Tilia americana), and sugar maple were the most important trees of the Slope Woods, where the Continuum Index reached 2253. Sugar maple dominated the sapling and seedling layers of both stands. American beech was completely absent from the Slope, while red oak was limited to minor status on the Plateau. The Slope Woods had a richer herb composition, with nearly twice as many species and nearly twice the cover of the Plateau. The Slope appeared to be undergoing the greatest change in tree species composition, with sugar maple apparently replacing the dominant red oak.
Keywords: Mayville Ledge Beech-Maple Woods State Natural Area; flora; vegetation survey